Occurrence of severe and moderate traumatic brain injury in patients attended in a Brazilian Teaching Hospital: Epidemiology and dosage of alcoholemy - De Faria, José Weber Vieira; Nishioka, Sérgio De Andrade; Arbex, Guilherme Leonel; Alarcão, Gustavo Gil; De Freitas, Wender Barbosa (FapUNIFESP (SciELO), 2008)
This study aimed at observing aspects of epidemiology in order to investigate the use of alcohol in patients older than 18 with severe and moderate traumatic brain injury, which were attended in the Clinics Hospital of the University of Uberlândia. Positive alcoholemy was found in 39.3% of the patients. Of the 33 positive exams alcoholemy was found higher than 60 mg/dL in 28 (84.6%). There was not significant relation between alcoholemy levels and trauma severity. The major prevalence occurred on Saturdays nights. The most frequent types of external causes were transportation accidents (64.74) followed by accidental falls (17.27%) and physical aggression (16.55%). 93.9% of the patients with positive alcoholemy were men aged 20-29. 24.2% of the ones with positive alcoholemy died yet no significant difference was found in the study of the ones with negative alcoholemy (n=51) (p=0.93); RR= 0.9; IC95%=0.40-2.08.
Keywords: Alcohol; Traumatic brain injury